2013
DOI: 10.1007/s11307-013-0626-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Biodistribution and Radiation Dosimetry of the Cannabinoid Type 2 Receptor Ligand [11C]-NE40 in Healthy Subjects

Abstract: This first-in-man study of [11C]-NE40 showed an expected biodistribution compatible with lymphoid tissue uptake and appropriate fast brain kinetics in the healthy human brain, underscoring the potential of this tracer for further application in central and peripheral inflammation imaging. The effective dose is within the typical expected range for 11C ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 34 publications
1
50
1
Order By: Relevance
“…Interestingly, there was no difference in CRIP1a mRNA, which has been previously reported to show an opposite regulation pattern as the CB 1 receptor (42). In contrast to receptor mapping studies over lifespan in humans, which find no changes in CB 2 receptor binding distribution with age in healthy individuals (43), we report that dorsal medullary CB 2 mRNA is increased in aged relative to younger SD rats. Expression of CB 2 receptors on brain microglia is upregulated during neuroinflammation (44), which may be the source of elevated CB 2 receptor mRNA in dorsal medulla of older rats detected by our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, there was no difference in CRIP1a mRNA, which has been previously reported to show an opposite regulation pattern as the CB 1 receptor (42). In contrast to receptor mapping studies over lifespan in humans, which find no changes in CB 2 receptor binding distribution with age in healthy individuals (43), we report that dorsal medullary CB 2 mRNA is increased in aged relative to younger SD rats. Expression of CB 2 receptors on brain microglia is upregulated during neuroinflammation (44), which may be the source of elevated CB 2 receptor mRNA in dorsal medulla of older rats detected by our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent findings have indicated that nicotine attenuates Aβ-induced microglial activation by shifting microglial M1 to M2 state, and cannabinoid CB2R mediates the process, thereby suggesting the CB2R involved in microglia polarization shift [112]. Several CB2R selective ligands have been developed over the past years [113] and the preliminary clinical evaluation with 11 C-NE40 showed appropriate fast brain kinetics in the healthy human brain [114]. However, 11 C-NE40 has not succeeded in highlighting microglial activation in AD subjects as compared to healthy controls.…”
Section: Potential Alternative Molecular Targets For Activated Micmentioning
confidence: 99%
“…2 In this context, the in vivo imaging of cannabinoid type 2 receptors (CB2R) with positron emission tomography (PET) might be crucial to further understand the role of these receptors on inflammatory reactions underlying brain diseases. Several PET radiotracers for CB2 receptors have been synthesized and tested preclinically, such as [ 23 Among them, [ 11 C]A-836339 has been suggested as a promising radiotracer for the in vivo evaluation of a neuroinflammatory reaction in both a systemic lipopolysaccharide (LPS)-induced mouse model of neuroinflammation and a mouse model of Alzheimer's disease. 22 In contrast, [ 11 C]NE40 has not shown to be sensitive enough to visualize the CB2 receptor expression after cerebral ischemia in mice in part due to its low affinity for CB2 receptors.…”
Section: Introductionmentioning
confidence: 99%